The Potential of Social Media in Increasing Young Generation's Legal Education - Suntara, Reza Adriantika; Satrio, Ndaru; Anwar, Muhammad Syaiful (Asatiza: Jurnal Pendidikan, 2024)
This research examines the role of social media in increasing legal awareness among the younger generation in Indonesia. As of January 2023, Indonesia had approximately 167 million social media users out of a total population of 276.4 million, highlighting a significant opportunity to enhance legal education. Despite this potential, the use of social media for raising legal awareness is minimal, reflected in high crime rates and low legal compliance. This study explores the urgency of legal education for the younger generation and the role social media can play in this effort. Using a literature review method, the research references relevant and reliable sources such as laws, books, journal articles, and official data. The meta-synthesis technique is applied to synthesize data from previous studies and draw conclusions. The findings indicate that legal education is crucial for improving legal awareness and compliance among the younger generation. Social media can significantly contribute by making legal information more engaging and accessible. The study recommends that the government utilize social media's potential in legal education by collaborating with private digital sectors and influencers to disseminate positive legal messages and raise awareness effectively.